The Critic’s Sketches, Criticism’s Inclination - Abdala Junior, Benjamin (Literatura e Sociedade, 2009)
The essay “Literatura e subdesenvolvimento” [“Literature and underdevelopment”], by Antonio Candido, was written as a response to the confinement imposed by the Brazilian military dictatorship (1964-1985). It points out to political-literary perspectives, situating Latin America as a cultural block and aiming to verify what is particular and what is common among the literatures produced in this region. The sense of Candido’s gesture can be apprehended, nowadays, in correlative critic inclinations, as long as we sense the necessity of thinking about supra-national communitarian blocks in order to face up to the asymmetries among cultural fluxes.